Synergistic Effect of Hyperglycemia and Suppression on Adult Mouse Islet Beta Cell Replication - Szu-Tah Chen; Shin-Huei Fu; Samuel Hsu; Yu-Yao Huang; Brend Ray-Sea Hsu (International Journal of Endocrinology, 2012)
The complementary role of hyperglycemia and suppression on islet beta cell regeneration was investigated in a syngeneic mouse model. gene silencing was performed by infecting islets of C57BL/6 with shRNA lentiviral particles. At 54 hours after viral infection, protein content in cultured targeting islets was 22% of that in freshly isolated islets. Six days after transplantation to diabetic mice, targeting islet graft had considerably more cells with Ki67-staining nuclei than nontargeting islets. The mice in the targeting-islet group had a significantly shorter duration of temporary hyperglycaemia than mice in the non-targeting-islet group. The long-term ex vivo beneficial effect of silencing on graft function was also indicated by the significantly higher cumulative cure rate for diabetes in mice receiving 200 targeting islets than that in mice receiving 200 non-targeting islets. Our data suggest that hyperglycemia and persistent suppression have a synergistic effect on islet beta cell replication in adult mice.